Perancangan Produk Portable untuk Make-up Artist - Stella Magnolia (Intra, 2017)
Practically, the purpose of this design is to create a portable product that practical and easy to carry anywhere. The benefits of this designs are to facilitate the community to complete their work needs to be more leverage. The product will be created in the form of product needed or needed by an MUA that is in the form of a suitcase that has the function of the chair also a folding table, also to put accessories makeup or other purposes as complement and tool for MUA. The method in this design uses primary data and secondary data by conducting initial interviews and direct observation and then followed by collecting data from literature studies related to this research. After the data collection is complete then proceed with analyzing the data already obtained. Next, start the design process up to the final stage while conducting discussions with the supervisor.